Central liver toxicity after SBRT: An expanded analysis and predictive nomogram. Issue 1 (January 2017) - Toesca, Diego A.S.; Osmundson, Evan C.; Eyben, Rie von; Shaffer, Jenny L.; Lu, Peter; Koong, Albert C.; Chang, Daniel T.
Abstract: Purpose: To further explore the correlation of central biliary tract (cHBT) radiation doses with hepatobiliary toxicity (HBT) after stereotactic body radiation therapy (SBRT) in a larger patient dataset. Methods: We reviewed the treatment and outcomes of all patients who received SBRT for primary liver cancer (PLC) and metastatic liver tumors between July 2004 and November 2015 at our institution. The cHBT was defined as isotropic expansions (5, 10, 15, 20 and 25 mm) from the portal vein (PV). Doses were converted to biologically effective doses by using the standard linear quadratic model with α / β of 10 (BED10 ). HBT was graded according to the Common Terminology Criteria for Adverse Events v4.03. Results: Median follow-up was 13 months. Out of the 130 patients with complete follow-up records analyzed, 60 (46.1%) had liver metastases, 40 (30.8%) had hepatocellular carcinoma (HCC), 26 (20%) had cholangiocarcinoma (CCA) and 4 (3.1%) patients other PLC histologies. Thirty-three (25.4%) grade 2+ and 28 (21.5%) grade 3+ HBT were observed. Grade 3+ HBT was seen in 13 patients (50%) with CCA, 7 patients (17.5%) with HCC and 7 (11.7%) patients with liver metastases. SBRT doses to the cHBT were highly associated with HBT, but only for PLC patients when analyzed by histological subtype. The 15 mm expansion from the PV (cHBT15 ) proved to be an appropriate surrogate for the cHBT. The strongest cHBT15 dose predictors for G3+ HBT for PLC were the VBED10 40 ⩾37 cc ( p  < 0.0001) and the VBED10 30 ⩾ 45 cc ( p  < 0.0001). Conclusion: SBRT doses to the cHBT are associated with occurrence of HBT only in PLC patients. Limiting the dose to the cHBT to VBED10 40 < 37 cc and VBED10 30 < 45 cc when treating PLC patients with SBRT may reduce the risk of HBT.